Laser spectroscopy of atoms : Two-frequency sub-Doppler spectroscopy of the caesium D1 line in various configurations of counterpropagating laser beams. (30th November 2020) - Brazhnikov, D V; Ignatovich, S M; Mesenzova, I S; Mikhailov, A M; Boudot, R; Skvortsov, M N
Abstract: Sub-Doppler resonances in caesium vapours are studied in a laser field produced by counterpropagating two-frequency light beams with mutually orthogonal linear polarisations. The beams are in resonance with optical transitions in the D1 line, the frequency difference of the field spectral components being equal to the hyperfine ground-state splitting in the Cs atom (≈9.2 GHz). It has already been shown that in this configuration, the hypercontrast effect can be observed for sub-Doppler resonances, which makes this configuration promising for the employment in newgeneration miniature optical frequency standards. In the present work, two different two-frequency configurations are compared with each other and with the single-frequency configuration widely used in practice for observing saturated absorption resonances. The parameters of nonlinear resonances are measured at various temperatures of caesium vapours and at different optical field intensities. The results of the investigations performed make it possible to find an optimal two-frequency scheme for exciting nonlinear resonances and to estimate a potential of the scheme for its applications in quantum metrology.